PREFERENSI HABITAT DAN RELUNG EKOLOGI KOMUNITAS IKAN TARGET DI SUNGAI KAPUAS BAGIAN HILIR - Adijaya, Mardan (Akuatik Tropis (Akuatrop): Journal of Tropical Aquatic Resource Management (ISSN:3063-7414), 2023)
The Kapuas River is one of the main rivers that supports potential fish resources in West Kalimantan. However, currently the development of the Kapuas River watershed is starting to appear to be influenced by ecological pressure from the agricultural and industrial sectors which has an impact on decreasing the potential of several target fish species. The aim of this research is to determine the habitat preferences and ecological niches of target fish communities in the lower reaches of the Kapuas River. Sampling was carried out using a purposive sampling method at 3 stations, namely the mouth of the Kapuas River in Jungkat and Sungai Raya, Kubu Raya Regency and the downstream part of the Kapuas River in Tayan Hilir, Sanggau Regency. Fish sampling was carried out using gill nets (5/9 inch mesh size) at each station with 3 repetitions set for 2 hours. At each station, samples were also taken of environmental factors consisting of substrate type, temperature, pH, DO and biological factors, namely plankton. The results of research on habitat preferences and ecological niches of fish communities in the lower Kapuas River show that there are 25 target fish species. The fish community in Terentang waters is different from the fish community in the Raya River and the Kapuas River mura in Jungkat. The main factor that influences community differences in the downstream Kapuas River is the amount of salinity. Ecological niche analysis shows that most of the target fish in the downstream Kapuas River are fish that are 55% carnivorous and the remaining 10% are carnivores, 20% are omnivores and 10% are herbivores. The types of fish food in the lower reaches of the Kapuas River mainly consist of phytoplankton, zooplankton, crustaceans, fish, molluscs and annelids.